Factors Affecting the Growth of Low Birth Weight Babies - Suyami Suyami; Lely Lusmilasari; Wahyudi Istiono (Asian Journal of Social and Humanities, 2023)
Birth weight is one of the determinants of a child's physical growth and future brain development. However, babies with low birth weight (LBW) are at risk of death and other health problems. The purpose of this literature review is to systematically summarize research that analyzes the factors that influence the growth of low birth weight babies. The method used was a literature review using the PRISMA Protocol, with inclusion criteria, namely full text and original research, the research subjects were babies born with low birth weight (<2500g), articles in Indonesian and English, published in the last 5 years (2017-2022). The results showed that there are several factors that influence the growth of infants with a history of low birth weight such as gender (male), lower gestational age, postnatal health problems, nutritional intake, such as exclusive breastfeeding or enteral feeding, and maternal parenting practices such as Kangaroo Mother Care (KMC). Exclusive breastfeeding and maternal parenting practices (Kangaroo Mother Care) have an impact on increasing growth so it is good to apply especially for mothers who have low-birthweight babies to catch up with age-appropriate growth.